Axial ligand engineering for highly efficient oxygen reduction catalysts in transition metal–N4 doped graphene. (5th August 2022) - She, Xuelian; Gao, Jinghan; Gao, Yan; Tang, Hao; Li, Kai; Wang, Ying; Wu, Zhijian
Abstract : Axial ligand engineering is a good strategy for enhancing the ORR activity. Abstract : Developing highly efficient and stable electrocatalysts for oxygen reduction reaction (ORR) is a challenging task in energy conversion technologies. In this work, diverse axial ligands have been used to modify the ORR activity of transition metal and nitrogen codoped graphene (MN4 -Gra). The weakening of the ORR intermediates by the axial ligand would activate these intermediates efficiently and improve the catalytic activity. Our study indicated that among the axial ligands adopted, nitrobenzene and benzene have good performance in improving the ORR activity. Several promising ORR catalysts are predicted. Among them, FeN4 -Gra modified by nitrobenzene, i.e., FeN4 -Gra/ben/NO2 has the best catalytic activity with a small overpotential of 0.21 V and energy barrier of 0.24 eV in the rate determining step, followed by RuN4 -Gra/ben/NO2 and FeN4 -Gra/benzene. These catalysts are also demonstrated to be stable by the calculated formation energies and dissolution potentials. The scaling relationships suggested that the adsorption energy of *OH and d band center would be good descriptors for predicting the highly efficient ORR catalysts. Therefore, axial ligand engineering would be a useful strategy to enhance the efficiency of ORR catalysts.